Barriers and facilitators affecting presentation in women with early versus advanced stage cervical cancer - Teresa K.L. Boitano; Mary A. Powell; Charles A. Leath, III; J. Michael Straughn, Jr; Isabel C. Scarinci (Elsevier, 2022)
Background: This study was performed to evaluate the barriers and facilitators associated with patient presentation for early stage (ES) versus advanced stage (AS) cervical cancer (CC). Methods: A mixed-method approach was used to collect quantitative (i.e., demographics and medical/screening histories) and qualitative data (individual interviews assessing patients' perceptions regarding their general health, HPV and CC screening, and barriers and facilitators to CC care). Two separate investigators coded the interviews for major themes that occurred with an agreement that 50% or more of the themes would be included. Results: Twenty-five women agreed to participate in the study with 80% completing the interview. Patients with ES disease were classified as Stage IA1-Stage IB3; patients with Stage IIA-IVB disease were classified with AS disease. Frequent barriers in the ES group were lack of knowledge, competing priorities, feeling healthy, lack of time or health insurance, and being embarrassed/uncomfortable. Frequent barriers in the AS group were lack of knowledge, competing priorities, avoidance/procrastination, fear of the healthcare system or finding something wrong, and lack of perceived risk to CC. Facilitators for ES included understanding the importance of the Pap test, having an abnormal Pap test, and knowing someone with CC. Having abnormal symptoms was the only facilitator for AS patients. Conclusions: Structural and intrapersonal barriers to CC care persist but differ between ES and AS patients. Multi-level interventions are needed to address the wide array of issues that women highlighted in this study including potential innovative methods to increase access to care and engagement with the healthcare system.